EVALUATING THE CONTENT VALIDITY OF THE ALGERIAN ENGLISH BACCALAUREATE EXAMINATION - Djedda TAKOUACHET; Mohammed NAOUA (Analele Universităţii din Craiova. Psihologie, Pedagogie)
In large-scale testing, validity stands out as a cornerstone in developing and evaluating tests. This is because it helps in designing tests that yield meaningful results. In this respect, this study seeks to examine whether the English tests of the BAC examination assessed the content that test designers intended to assess. To achieve so, the present article employs a descriptive content analysis, following Bachman and Palmer’s model of test usefulness. The data are analysed through curriculum mapping to compare test tasks against learning objectives. Importantly, the obtained results have revealed partial content validity as the exam aligns adequately with the curriculum content. The findings highlight key strengths and gaps in the test’s design. Thus, a list of recommendations are offered to strengthen the two validities in the English Baccalaureate tests.